2015
DOI: 10.1021/bi5015216
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Difference in Human IgG2 Disulfide Isoforms Revealed by Hydrogen/Deuterium Exchange Mass Spectrometry

Abstract: Both recombinant and natural human IgG2 antibodies have several different disulfide bond isoforms, which possess different global structures, thermal stabilities, and biological activities. A detailed mapping of the structural difference among IgG2 disulfide isoforms, however, has not been established. In this work, we employed hydrogen/deuterium exchange mass spectrometry to study the conformation of three major IgG2 disulfide isoforms known as IgG2-B, IgG2-A1, and IgG2-A2 in two recombinant human IgG2 monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…These results reveal that the A1 form is not stable under the conditions of the chromatographic separation. This is consistent with a recent report that the A1 form is the least stable IgG2 isoform due to less protection of the disulfide bond [26]. These data in Figure2a and 2b support a conclusion that the conditions of reversed phase chromatography are capable of changing the sample composition for a sufficiently high concentration of the A1 isoform, but not for IgG2 concentrations typically used.…”
Section: Resultssupporting
confidence: 92%
“…These results reveal that the A1 form is not stable under the conditions of the chromatographic separation. This is consistent with a recent report that the A1 form is the least stable IgG2 isoform due to less protection of the disulfide bond [26]. These data in Figure2a and 2b support a conclusion that the conditions of reversed phase chromatography are capable of changing the sample composition for a sufficiently high concentration of the A1 isoform, but not for IgG2 concentrations typically used.…”
Section: Resultssupporting
confidence: 92%
“…Detection of these species after disruption of all hinge disulfides indicates the presence of strong noncovalent forces between the HCs, in alignment with the extensive Fab-Fab and Fab-C H 2 interactions previously reported for the B isoform. 26,51 Our observed disulfide isoform conversion directionality is in agreement with previous studies that have reported conversion of the A → A/B → B forms in a reducing environment similar to physiological conditions. 24,25 The higher thermal stability of the IgG2-B mAb and ADCs observed in this study provides further evidence that IgG2 disulfide scrambling favors the thermodynamic product.…”
Section: Discussionsupporting
confidence: 92%
“…21,22 The higher-order structural differences at the Fab/C H 2 interface of the IgG2 isoforms affect the solvent accessibilities of the interchain disulfides. 26,27 One consideration for the ADC manufacturing process is the potential for disulfide bond rearrangement, which can occur at the preferred pH range for the partial reduction and conjugation reactions. [28][29][30][31][32] The rate of intramolecular thiol-disulfide exchange is accelerated when the conditions favor the degradation of disulfides and the formation of the thiolate anion, such as under the presence of a reducing reagent or in neutral or alkaline environments.…”
Section: Introductionmentioning
confidence: 99%
“…Potential approaches that capture this information include NMR, 13 EPR, 14 single molecule spectroscopy, 15,16 ion mobility mass spectrometry (IM-MS) 17 and hydrogen/deuterium (H/D) exchange mass spectrometry. 18 However, at present these approaches are not in routine use due to significant technical complexity and feasibility, instrument expense, time of assay, complex sample preparation and need for specialist analysis. Instead, a breadth of lower resolution approaches such as far-UV circular dichroism (CD), used to detect changes in protein secondary structure, and light scattering or size exclusion chromatography (SEC), are used to detect aggregation.…”
Section: Introductionmentioning
confidence: 99%